SSM Basic Mathematics 6e - Sippel, Sheryl W. (Brooks/Cole, 2005)
Chapter 1: Whole Numbers- Chapter 2: Fraction and Mixed Number - Chapter 3: Decimals - Chapter 4: Ratio and Proportion - Chapter 5: Percent - Chapter 6: Measurement - Chapter 7: Introduction to Algebra - Chapter 8: Sloving Equations